Theoretical Mapping of Suicidal Risk Factors During the COVID-19 Pandemic: A Mini-Review - Raj, Saurabh; Ghosh, Debasruti; Singh, Tushar; Verma, Sunil K.; Arya, Yogesh K. (Frontiers in Psychiatry, 2021)
Suicide prevention in times of COVID-19 pandemic has become more challenging than ever due to unusual circumstances. The common risk factors identified with regard to suicidal behavior are fear of COVID-19, economic instability, poor access to healthcare facilities, pre-existing psychiatric disorders, and social disconnect. The studies done so far have reported either case studies or have made an effort to understand the risk factor. An understanding of the underlying causal pattern from existing theories, behind these risks, will enable adopting appropriate prevention mechanisms. Hence, this review examines evidence related to risk factors of suicides that occurred during COVID 19 and discusses it in the light of three major theoretical approaches: interpersonal model, stress diathesis model, and cognitive model. The insights obtained from the three viewpoints reveal that perceived burdensomeness, thwarted belongingness, stress sensitivity, cognitive errors such as magnification, catastrophization, arbitrary inference, and mind-reading are likely reasons behind these risk factors for suicide. It is suggested that awareness regarding COVID-19 stressors, use of community-based approaches like gatekeeper training, and brief online psychotherapy by using techniques of mindfulness, interpersonal psychotherapy, and cognitive behavior therapy can be useful in reducing suicidal risk during COVID-19.